2013
DOI: 10.1111/jdv.12165
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in psoriasis: a systematic review and meta‐analysis of epidemiological studies

Abstract: The relationship between psoriasis and increased cancer risk is debated.The aim of this study was to evaluate if there is an increase in the background risk of cancer in psoriasis patients compared with the general population. A systematic literature search was performed on PubMed, Embase and Cochrane databases, using the keywords 'Pso- Of the 1080 articles retrieved, 37 references were selected. There may be an increased risk of some solid cancers in psoriasis: respiratory tract cancer [standardized incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
209
3
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(242 citation statements)
references
References 46 publications
12
209
3
5
Order By: Relevance
“…Notably, patients with psoriasis have an increased risk of squamous cell carcinoma (SIR = 5.3; 95% CI 2.63-10.71) and basal cell carcinoma (SIR = 2.00; 95% CI 1.83-2.20), but not melanoma (SIR = 1.07; 95% CI 0.85-1.35) [26].…”
Section: Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, patients with psoriasis have an increased risk of squamous cell carcinoma (SIR = 5.3; 95% CI 2.63-10.71) and basal cell carcinoma (SIR = 2.00; 95% CI 1.83-2.20), but not melanoma (SIR = 1.07; 95% CI 0.85-1.35) [26].…”
Section: Cancersmentioning
confidence: 99%
“…Results from a meta-analysis of epidemiologic studies in patients with psoriasis found that the standardized incidence ratio (SIR) of any cancer, excluding nonmelanoma skin cancer (NMSC), was 1.16 (95% confidence interval [CI] 1.07-1.25) [26]. Notably, patients with psoriasis have an increased risk of squamous cell carcinoma (SIR = 5.3; 95% CI 2.63-10.71) and basal cell carcinoma (SIR = 2.00; 95% CI 1.83-2.20), but not melanoma (SIR = 1.07; 95% CI 0.85-1.35) [26].…”
Section: Cancersmentioning
confidence: 99%
“…Another meta-analysis found an increased risk of the development of various forms of cancer [69]. PUVA treatment increases the risk of cutaneous squamous cell carcinoma and malignant melanoma.…”
Section: Sheets For the Presentationmentioning
confidence: 99%
“…An increased risk of skin cancer also exists with psoralen and ultraviolet-A (PUVA) or NB-UVB [4]. However, other comorbidities such as tobacco smoking and alcohol use must be considered when measuring the cancer risk in psoriasis [5]. Our patient had received cyclosporine and NB-UVB phototherapy, but no other comorbidities such as tobacco smoking, betel nut chewing, or alcohol use were identified.…”
Section: Introductionmentioning
confidence: 99%